Unusual Pancreatico-Mesenteric Vasculature: A Clinical Insight - Shikha Singh; Jasbir Kaur; Jyoti Arora; Renu Baliyan Jeph; Vandana Mehta; Rajesh Kumar Suri (Archives of Anatomy and Physiology - Peertechz Publications, 2016)
Background: Awareness about the variable vascular anatomy of superior mesenteric artery is imperative for appropriate clinical management. Present study not only augments anatomical literature pertaining to mesenteric vasculature but also adds to the clinical acumen of medical practitioners in their clinical endeavors. Case summary: The present study reports the occurrence of anomalous branch, termed as accessory inferior pancreatic artery stemming from superior mesenteric artery. Additionally inferior pancreaticoduodenal artery was seen to be dividing into right and left branches instead of usual anterior and posterior branches. Right branch terminated by anastomosing with anterior branch of superior pancreaticoduodenal artery whereas left branch supplied the proximal part of the jejunum. Anomalous course of anterior branch of superior pancreaticoduodenal artery was also seen. Conclusion: Knowledge of anomalous and variable branching pattern of superior mesenteric artery is crucial while performing various surgical and radiological procedures as it helps in minimising the intraoperative as well as postoperative complicationsCase summary: The present study reports the occurrence of anomalous branch, termed as accessory inferior pancreatic artery stemming from superior mesenteric artery. Additionally inferior pancreaticoduodenal artery was seen to be dividing into right and left branches instead of usual anterior and posterior branches. Right branch terminated by anastomosing with anterior branch of superior pancreaticoduodenal artery whereas left branch supplied the proximal part of the jejunum. Anomalous course of anterior branch of superior pancreaticoduodenal artery was also seen. Conclusion: Knowledge of anomalous and variable branching pattern of superior mesenteric artery is crucial while performing various surgical and radiological procedures as it helps in minimising the intraoperative as well as postoperative complications.